INFECTION THAT UNDERLIES THE OCCURRENCE OF FEBRILE SEIZURES: A CASE REPORT OF A 2-YEAR-OLD BOY WITH COMPLEX FEBRILE SEIZURE - Dimas Tri Anantyo; Ayu Anggraini Kusumaningrum; Nuh Gusta Ady Yolanda; Vinandra - (Jurnal Kedokteran Diponegoro, 2021)
Background: Febrile seizures are seizures associated with fever during childhood that most often occurs in children ages six months-five years, with a peak incidence of 18 months Although febrile seizures generally have a good prognosis, they can signal an underlying serious acute infectious infection. This report aims to present a case of febrile seizures associated with the underlying extracranial infection in Semarang.